Social work, human rights and conceptions of human dignity: The case of social workers in Lisbon - Moema Bragança Bittencourt; Amaro, M. I. (Portuguese Journal of Social Science, 2019)
This article seeks to explore the conception of human dignity prevailing among social workers in Lisbon through a qualitative-type study. This departs from analysis of the concepts of humanity and the rule of law as guarantees for exercising social work in order to locate the concept of human dignity as a historical, social and cultural construct. The qualitative analysis of the data collected by interviews demonstrates that social workers, while not having a deep-reaching conceptual understanding of this theme, prioritize a Kantian conception of human dignity, perceiving this as an absolute value